Internal maxillary artery pseudoaneurysm in a case of mandibular fracture - K. Karanth Siddharth; Jagannathan Mukund; S. G. Mahesh; Devale Maksud (Indian Journal of Plastic Surgery)
We report a rare case of internal maxillary artery pseudoaneurysm in a patient with a subcondylar fracture of the mandible. Though traumatic pseudoaneurysm in the craniofacial region is a known entity, a situation in which a closed mandibular fracture presents as a rapidly growing swelling in the neck and facial region is a rare presentation. Such a warning sign should be taken seriously and investigated further.